A case of cushings disease evaluated by Inferior petrosal sinus sampling a novel Approach in bangladesh - Prasad, Indrajit; Ansari, MA Jalil; Rahman, Kazi Mohibur; Saha, Joysree; Hossain, Mohammad Zaid; Talukder, Debesh Chandra (Journal of Dhaka Medical College, 2013)
A 16 years old boy presented to the Department of Endocrinology, Sir Salimullah Medical College & Mitford Hospital with the complaints of occasional headache, vomiting and gradual weight gain for the last 5 years. He was overweight & has moon face, lipomastia, striae over the abdomen. His random blood sugar was 15 mmol/l, serum potassium was low, no suppression of serum cortisol on low dose 1mg dexamethasone suppression test (297 nmol/l)(cut of <140 nmol/l), loss of diurnal rhythm of serum cortisol (morning 430 nmol/l, midnight 992 nmol/l), 24h urinary free cortisol in the upper limit of normal (164mcg), modest elevation of serum adrenocorticotropic hormone (ACTH) (59.7 pg/ml), no significant gradient of serum ACTH level between internal jugular and femoral vein, normal adrenal glands on computed tomography (CT) abdomen, pituitary microadenoma on magnetic resonance imaging (MRI) of Sella. On above clinical examination and, investigation he was diagnosed as Cushings disease with diabetes mellitus. This patient was referred to department of neurosurgery for surgical management. The patient is now on medical treatment. Ketoconazole for hypercortisolism, lifestyle modification and metformin for diabetes mellitus. He is expected to have the neurosurgical treatment shortly. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15708 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 96-101